2023
DOI: 10.1186/s13020-023-00735-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological effects of gallic acid: current perspectives

Abstract: Gallic acid (GA) is a phenolic molecule found naturally in a wide range of fruits as well as in medicinal plants. It has many health benefits due to its antioxidant properties. This study focused on finding out the neurobiological effects and mechanisms of GA using published data from reputed databases. For this, data were collected from various sources, such as PubMed/Medline, Science Direct, Scopus, Google Scholar, SpringerLink, and Web of Science. The findings suggest that GA can be used to manage several n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 176 publications
1
24
0
Order By: Relevance
“…Inflammation plays a key role in the host's defense against pathogens, but it is also essential for the repair of tissues, regeneration, and reconstruction, and subtle forms of inflammation are indispensable for the maintenance of tissue homeostasis. [91,92] Studies have shown that both chronic and acute inflammatory processes strongly influence cancer development. Advances in inflammation research have uncovered a link between inflammatory processes and neoplastic transformation, tumor development, and the progression of metastases and recurrences.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…Inflammation plays a key role in the host's defense against pathogens, but it is also essential for the repair of tissues, regeneration, and reconstruction, and subtle forms of inflammation are indispensable for the maintenance of tissue homeostasis. [91,92] Studies have shown that both chronic and acute inflammatory processes strongly influence cancer development. Advances in inflammation research have uncovered a link between inflammatory processes and neoplastic transformation, tumor development, and the progression of metastases and recurrences.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…This results in chemical chain reactions (called oxidation reactions) that can have beneficial or harmful consequences (Calina et al, 2020;Mititelu et al, 2020;Islam et al, 2021;Amin et al, 2022). Due to their chelating ability and antioxidant activity many compounds can act as regulators of heme iron excess, avoiding oxygen-initiated free radical formation and, ultimately, preventing damaging Fenton reactions (Nussbaum et al, 2017;Buga et al, 2019;Calina et al, 2020;Bhuia et al, 2023). Furthermore, inositol hexaphosphate (IP6) also proved to be effective in reducing the occurrence of metal-catalyzed protein glycation, such as advanced glycation end products (AGEs), which may trigger diabetes-related diseases (López-Moreno et al, 2022).…”
Section: Phytate As Antioxidantmentioning
confidence: 99%
“…By reacting with almost all of the molecules present in living cells, including DNA, these reactive species cause oxidative damage [52,53] . Elevated levels of intrinsic or extrinsic free radicals and high levels of lipid peroxides, which are the etiology of several degenerative conditions including atherosclerosis, cancer, diabetes, Alzheimer's disease, cataracts, aging, and so on, are produced by excess ROS if the antioxidant system is not able to remove them [50,54] . Consequently, to maintain the antioxidant system, different synthetic antioxidants including butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA), and propyl gallate (PG) have been used, but these are not safe, accessible, and affordable [55] .…”
Section: Traditional Usesmentioning
confidence: 99%
“…[52,53] Elevated levels of intrinsic or extrinsic free radicals and high levels of lipid peroxides, which are the etiology of several degenerative conditions including atherosclerosis, cancer, diabetes, Alzheimer's disease, cataracts, aging, and so on, are produced by excess ROS if the antioxidant system is not able to remove them. [50,54] Consequently, to maintain the antioxidant system, different synthetic antioxidants including butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA), and propyl gallate (PG) have been used, but these are not safe, accessible, and affordable. [55] As a result of the serious effects of OS and the limitations of synthetic antioxidants, there is a demand for replacement antioxidants compounds that are safer, and easily accessible, as well as potent.…”
Section: Antioxidant Activitymentioning
confidence: 99%